Relationship Between Hemodialysis Adequacy and Quality Of Life of Chronic Renal Failure Patients in RSU. Royal Prima Medan in 2022 - Chairunnisa Novinka; Delpianus Gea; Fadhilla Fadsya; Nurmala Sari; Ritha Meicindy Br. Tarigan; Tiarnida Nababan (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
More than 750 million additional persons are added to the world population each year due to the prevalence of chronic renal disease. The Global Burden of Chronic Kidney Disease Study conducted in 2017 found that chronic kidney disease is directly responsible for roughly 2.59 million deaths worldwide caused by impaired kidney function. Dialysis is a life-prolonging treatment that is administered to about 78.8 percent of chronic renal failure patients across the world. The purpose of this research is to evaluate whether or not there is a correlation between the appropriateness of hemodialysis treatment and the quality of life of patients with chronic renal failure who are receiving treatment at the RSU. Royal Prima Medan 2022. Methodologies such as descriptive analysis and cross-sectional research are utilized in this kind of investigation. In this study, a total of 25 people were randomly selected for participation in the study using the accidental sampling approach. According to the findings of the chi-square test, which had df = 2 and a p value that was less than 0.05, the hypothesis of Ho was not supported. As a consequence of this, the provision of proper hemodialysis has a significant bearing on the quality of life enjoyed by patients who suffer from chronic renal failure. It is anticipated of respondents that they will have an understanding of the function and purpose of the hemodialysis adequacy process in line with the recommendations for hemodialysis prescriptions in order to attain a good quality of life.